Correction: India can consider integration of three eliminable disease control programmes on malaria, lymphatic filariasis, and visceral leishmaniasis. - Manju Rahi; Rini Chaturvedi; Payal Das; Amit Sharma (PLoS Pathogens, 2022)
[This corrects the article DOI: 10.1371/journal.ppat.1009492.].